Aortic Stiffness, Left Ventricle Hypertrophy, and Homogeneity of Ventricle Repolarization in Adult Dialyzed Patients - Tomasz Zapolski; Andrzej Jaroszyński; Anna Drelich-Zbroja; Anna Wysocka; Jacek Furmaga; Andrzej Wysokiński; Andrzej Książek; Małgorzata Szczerbo-Trojanowska; Sławomir Rudzki (The Scientific World Journal)
Aim. Study was designed to assess relationship between aortic compliance and homogeneity of heart electrical activity in dialysis patients. Methods. Study group was consisted of 120 dialyzed patients; 57 (age 50,7±7,1) were on continuous ambulatory peritoneal dialysis (CAPD) and 73 (age 51,6±7,6) were hemodialyzed (HD). Three-dimensional vectorocardiographic (VCG) monitoring was done to assess: QRS-𝑇angle, 𝑇el and 𝑇az. Echocardiography was performed to assess: Aomax, Aomin, ASI (aortic siffness index). Results. ASI in HD as well as in CAPD patients was significantly higher compared to controls [resp., 5,51 (±1,32), 5,83 (±1,41), 3,07 (±1,09)]. Cut-off value of ASI was 5,67. In HD patients strong correlations between ASI and QRS-𝑇angle, 𝑇el and 𝑇az were determined (resp., 𝑟=0,429, 𝑃<0,001; 𝑟=0,432, 𝑃≤0,001 and 𝑟=0,387, 𝑃=0,001). In CAPD group were significant association between ASI and QRS-𝑇angle, 𝑇el and 𝑇az (resp., 𝑟=0,452, 𝑃<0,001; 𝑟=0,417, 𝑃<0,001 and 𝑟=0,390, 𝑃=0,001). ASI was independently and markedly associated with: QRS-𝑇angle, 𝑇elev, 𝑇az, ADMA, cTnT, CRP, Total-chol, LDL-chol in HD and CAPD patients. Conclusions. ASI and VCG indices are higher in HD and CAPD patients. Correlation between ASI and VCG parameters may reflect unfavourable influence of poor aortic compliance on the electrical activity of the heart in dialyzed patients. Hypertrophy aggravates repolarization disturbances in hemodialyzed patients.